Comparative Istanbul example regarding attitudes of the students preparing for university exam towards mathematics and computer - Korkmaz, M., Çelebi, N., Yücel, A. S., Ceim, D. T., (My University, 2014)
The purpose of this study is to determine mathematics and computer attitudes of the students preparing for university exam. In this sense, the questionnaire was performed on a total of 250 people. Cronbach’s alpha analysis was applied for the reliability of the questions prepared, and the reliability coefficient was found 0.920. Factor analysis, regression test, chi-square, t test and one-way Anova tests were utilized in the analysis of data obtained In summary, it has been concluded that the success average of the participants for math lesson is high and their daily internet use is 4 hours and above. The students have stated that the technology increases their success in their lessons but they waste their time with internet use instead of using their time to prepare university exam. The parents of the students have put forward their negative concerns about the use of technology due to the worries for the exam.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mathematics; Computer; Attitude; Computer Technologies